2021
DOI: 10.3389/fpsyg.2021.736002
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Pandemic Changes the Nudging Effect of Social Information on Individuals' Blood Donation Intention

Abstract: The positive effect of social information on nudging prosocial behavior is context dependent. Understanding how sensitive intervention outcomes are to changes in the choice context is essential for policy design, especially in times of great uncertainty, such as the current COVID-19 pandemic. The present paper explores the effectiveness of social information in changing voluntary blood donation intention in two contexts: before and after the peak of the COVID-19 pandemic in China. In addition to the dimension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…As a result of an altruistic behavior donors have demonstrated a moral concern for the well‐being of others, instead of theirs's own, which in turn has translated into a positive attitude toward helping others (Graça & Zwick, 2021). Additionally, it may be also possible that this return to normality could be a consequence of the greater emphasis on donor orientation of BTCS during the pandemic using information strategies, retention and recruitment strategies, spreading awareness on volunteer blood donation, as well as analyzing the motivations and barriers to donating blood (Bilancini et al, 2022; Kakaje et al, 2023; Tripathi et al, 2022; Veseli et al, 2022; Wang et al, 2021). Particularly, Quee et al (2022) research about blood donor's motivators during the COVID pandemic in Netherlands state that whole blood donors (90.8%) were motivated by the calls for donation, which shows the importance of explicitly expressing need in times of crisis by blood banks and philanthropic organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of an altruistic behavior donors have demonstrated a moral concern for the well‐being of others, instead of theirs's own, which in turn has translated into a positive attitude toward helping others (Graça & Zwick, 2021). Additionally, it may be also possible that this return to normality could be a consequence of the greater emphasis on donor orientation of BTCS during the pandemic using information strategies, retention and recruitment strategies, spreading awareness on volunteer blood donation, as well as analyzing the motivations and barriers to donating blood (Bilancini et al, 2022; Kakaje et al, 2023; Tripathi et al, 2022; Veseli et al, 2022; Wang et al, 2021). Particularly, Quee et al (2022) research about blood donor's motivators during the COVID pandemic in Netherlands state that whole blood donors (90.8%) were motivated by the calls for donation, which shows the importance of explicitly expressing need in times of crisis by blood banks and philanthropic organizations.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of an altruistic behavior donors have demonstrated a moral concern for the wellbeing of others, instead of theirs's own, which in turn has translated into a positive attitude toward helping others (Graça & Zwick, 2021). Additionally, it may be also possible that this return to normality could be a consequence of the greater emphasis on donor orientation of BTCS during the pandemic using information strategies, retention and recruitment strategies, spreading awareness on volunteer blood donation, as well as analyzing the motivations and barriers to donating blood (Bilancini et al, 2022;Kakaje et al, 2023;Tripathi et al, 2022;Veseli et al, 2022;Wang et al, 2021 donors in order to create marketing strategies that address their values and promote sustainable involvement, with an especial attention to philanthropy as an intrinsic motivation in young people attitudes and intent to donate (Gorczyca & Hartman, 2017;Graça & Zwick, 2021). Therefore, the importance of reinforcing donor orientation of BTCS (and the internal social capital mechanisms that support this orientation) seems evident in a world where blood donation need is increasingly higher.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…First, at the ideological level, blood banks encouraged people to participate in blood donation by issuing public service announcements and sending blood demand information to the public. Some studies have highlighted that an official information source has a greater influence on participants’ intentions behind donation than an unofficial source 51 and that social media publicity motivates more people to donate blood. 52 Second, at the organizational level, the government and blood banks worked together to mobilize the city’s organizations and their employees to participate in group blood donations.…”
Section: Discussionmentioning
confidence: 99%
“…Individual processing of social information is affected by contextual factors such as emotion. [31][32][33] Studies have found that citizens' emotions changed according to the status of the COVID-19 pandemic, 34,35 resulting in different perceptions of identical social information. While quarantine is considered especially effective for reducing infections and mortality, and has been implemented in most countries during the pandemic, 36,37 this policy diminishes social opportunities and aggravates loneliness and feelings of uncertainty, leading to higher levels of social anxiety.…”
Section: Social Anxiety As a Mediatormentioning
confidence: 99%